Oxygenator Impact on Ceftaroline in Extracorporeal Membrane Oxygenation Circuits. Issue 11 (November 2018) - Cies, Jeffrey J.; Moore, Wayne S.; Giliam, Nadji; Low, Tracy; Enache, Adela; Chopra, Arun
Abstract : Objectives: To determine the oxygenator impact on alterations of ceftaroline in a contemporary neonatal/pediatric (1/4-inch) and adolescent/adult (3/8-inch) extracorporeal membrane oxygenation circuit including the Quadrox-i oxygenator (Maquet, Wayne, NJ). Design: Quarter-inch and 3/8-inch, simulated closed-loop extracorporeal membrane oxygenation circuits were prepared with a Quadrox-i pediatric and Quadrox-i adult oxygenator and blood primed. Additionally, 1/4-inch and 3/8-inch circuits were also prepared without an oxygenator in series. An one-time dose of ceftaroline was administered into the circuits, and serial pre- and postoxygenator concentrations were obtained at 5 minutes, 1-, 2-, 3-, 4-, 5-, 6-, and 24-hour time points. Ceftaroline was also maintained in a glass vial, and samples were taken from the vial at the same time periods for control purposes to assess for spontaneous drug degradation. Setting: A free-standing extracorporeal membrane oxygenation circuit. Patients: None. Intervention: Single dose administration of ceftaroline into closed-loop extracorporeal membrane oxygenation circuits prepared with and without an oxygenator in series with serial preoxygenator, postoxygenator, and reference samples obtained for concentration determination over a 24-hour study period. Measurements and Main Results: For the 1/4-inch circuit with an oxygenator, there was 79.8% drug loss preoxygenator and 82.5% drug loss postoxygenator at 24 hours. There was a statistically significant difference ( p < 0.01) in the amount of ceftaroline remaining at 24 hours when compared with each prior time point for the 1/4-inch circuit. For the 1/4-inch circuit without an oxygenator, there was no significant drug loss at any study time point. For the 3/8-inch circuit with an oxygenator, there was 76.2% drug loss preoxygenator and 77.6% drug loss postoxygenator at 24 hours. There was a statistically significant difference ( p < 0.01) in the amount of ceftaroline remaining at 24 hours when compared with each prior time point for the 3/8-inch circuit. For the 3/8-inch circuit without an oxygenator, there was no significant drug loss at any study time point. The reference ceftaroline concentrations remained relatively constant during the entire study period demonstrating the ceftaroline loss in each size of the extracorporeal membrane oxygenation circuit with or without an oxygenator was not a result of spontaneous drug degradation and primarily the result of the oxygenator. Conclusions: This ex vivo investigation demonstrated significant ceftaroline loss within an extracorporeal membrane oxygenation circuit with an oxygenator in series with both sizes of the Quadrox-i oxygenator at 24 hours. Therapeutic concentrations of ceftaroline in the setting of extracorporeal membrane oxygenation may not be achieved with current U.S. Food and Drug Administration-recommended doses, and further evaluation is needed before specific drug dosing recommendations can be made for clinical application with extracorporeal membrane oxygenation.